Perspektiven des Medizinrechts im 21. Jahrhundert - Duttge, Gunnar (Universitätsverlag Göttingen, 2007)
Series "Göttinger Schriften zum Medizinrecht" (medicine law), which deals with several important debates in modern medicine such as gene therapy, research with embryonic stem cells, bio databases, living organ donation, and in general the economisation of the health system.